High Performance Liquid Chromatographic-UV Method for Determination of Atorvastatin Calcium in Pharmaceutical Formulations - Najmul Hejaz Azmi, Syed; Khalifa Al-Mamari, Amna; Said Al-Hosni, Buthaina; Rashied Al-Fazari, Manal (Journal of New Developments in Chemistry, 2017)
The effectiveness of atorvastatin calcium in lowering cholesterol is dose-related. It is available in 10, 20, 40, and 80 mg film coated tablets. In order to ensure quality, safety and efficacy of tablets in formulations, the objective of this presented work was to develop a new high performance liquid chromatographic-UV method for quantitation of active atorvastatin calcium in pharmaceutical formulations. The method was based on reversed-phase high performance liquid chromatographic-UV separation of atorvastatin at detection wavelength of 246 nm using Acclaim 120 C18 reversed phase LC column (5 mm, 250×4.6 mm) with mobile phase of acetonitrile-dichloromethane-acetic acid (68.6: 30.6: 0.8 v/v/v) at a flow rate of 1.0 mL min-1 at 25°C. Different variables affecting chromatographic separation were carefully studied and optimized. The study results provided chromatogram of atorvastatin with retention time of 2.68 min. The calibration curve was linear over the concentration range of 15-300 mg mL-1. No interference was observed from common pharmaceutical excipients present in dosage forms. The proposed method was successfully applied to the determination of atorvastatin calcium in pharmaceutical formulations and proved to be significantly not different with reference method. The proposed can be used as an alternate method for routine quality control analysis of active atorvastatin in research, hospitals and pharmaceutical laboratories.
Keywords: Atorvastatin calcium; high performance liquid chromatography; validation; drug formulations